A New Route for the Synthesis of Quinazolinones - Mishra, AD (Nepal Journal of Science and Technology, 2012)
Quinazolinone derivatives are highly bioactive heterocyclic compounds with wider range of microbial activities such as anti-malarial, anti-cancer, anti-inflammatory, anti-hypertensive, anti-convulsant, anti-HIV, etc. Solid supported microwave synthesis of some 3-substituted-4-(2H)-quinazolinones has been carried out by the reaction of anthranilic acid, formaldehyde and primary aromatic amines. The usage of hazardous reagents and organic solvents has been avoided. The reactions were conducted in presence of acidic alumina where formaldehyde entered into cycloaddition to yield the quinazolinone derivatives. The reactions completed within 2-4 minutes with 82-94% of yields in microwave reactions while it took 5-7 hours for completion affording only 56-68% of the yields in conventional reactions. The synthesized quinazolinone derivatives showed moderate to promising antibacterial and antifungal activities. DOI: http://dx.doi.org/10.3126/njst.v12i0.6491 Nepal Journal of Science and Technology 12 (2011) 133-138